Distinct roles for FOXP3 and FOXP3 CD4 T cells in regulating cellular immunity to uncomplicated and severe Plasmodium falciparum malaria. - Michael Walther; David Jeffries; Olivia C Finney; Madi Njie; Augustine Ebonyi; Susanne Deininger; Emma Lawrence; Alfred Ngwa-Amambua; Shamanthi Jayasooriya; Ian H Cheeseman; Natalia Gomez-Escobar; Joseph Okebe; et al. (PLoS Pathogens)
Failure to establish an appropriate balance between pro- and anti-inflammatory immune responses is believed to contribute to pathogenesis of severe malaria. To determine whether this balance is maintained by classical regulatory T cells (CD4(+) FOXP3(+) CD127(-/low); Tregs) we compared cellular responses between Gambian children (n = 124) with severe Plasmodium falciparum malaria or uncomplicated malaria infections. Although no significant differences in Treg numbers or function were observed between the groups, Treg activity during acute disease was inversely correlated with malaria-specific memory responses detectable 28 days later. Thus, while Tregs may not regulate acute malarial inflammation, they may limit memory responses to levels that subsequently facilitate parasite clearance without causing immunopathology. Importantly, we identified a population of FOXP3(-), CD45RO(+) CD4(+) T cells which coproduce IL-10 and IFN-gamma. These cells are more prevalent in children with uncomplicated malaria than in those with severe disease, suggesting that they may be the regulators of acute malarial inflammation.